2016
DOI: 10.1016/j.cub.2016.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Individual Identifiability Predicts Population Identifiability in Forensic Microsatellite Markers

Abstract: Highly polymorphic genetic markers with significant potential for distinguishing individual identity are used as a standard tool in forensic testing [1, 2]. At the same time, population-genetic studies have suggested that genetically diverse markers with high individual identifiability also confer information about genetic ancestry [3-6]. The dual influence of polymorphism levels on ancestry inference and forensic desirability suggests that forensically useful marker sets with high levels of individual identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 43 publications
8
60
1
3
Order By: Relevance
“…We endorse the concerns thoroughly discussed [8], which emerge from this perhaps unwanted property of such markers. Mathematically, the degree of population identifiability may have a non-null impact on calculations of the posterior probability of individual assignment.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We endorse the concerns thoroughly discussed [8], which emerge from this perhaps unwanted property of such markers. Mathematically, the degree of population identifiability may have a non-null impact on calculations of the posterior probability of individual assignment.…”
Section: Discussionsupporting
confidence: 71%
“…Some loci contributed to the same sPC with more than one allele, a not unexpected finding in view of the intrinsic negative correlation between the frequencies of alternative alleles at the same locus. Finally, only in 9 out of 16 loci the most frequent allele emerged, confirming that a relevant spatial signal was often due to alleles that contribute only marginally to the overall variance [8]. These observations suggested that some loci, and some of their alleles, convey a clearer signal of spatial structuring, and one or more reduced datasets can be obtained, which could retain most of the geographic information but with an abated background noise.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Increasing interest within both the scientific and public communities in the ancestral origins of modern humans has led to significant advances in how we seek to understand the genetic history of global populations and their members using a variety of data types (Creanza et al, 2015;Hellenthal et al, 2014;Henn, CavalliSforza, & Feldman, 2012;Manica, Amos, Balloux, & Hanihara, 2007). In recent years, focus in human genetics has shifted accordingly toward large-scale genomic analyses of complex population histories, including ancient and forensic samples, and previously underserved populations (Algee-Hewitt, Edge, Kim, Li, & Rosenberg, 2016;Moreno-Estrada et al, 2014;Raghavan et al, 2015). With this emphasis on human history and the expansion of research potential that genomics has brought to the fundamental questions of anthropology, genetic analyses are now approximating the kinds of information that anthropologists have historically estimated from visible or measurable traits.…”
Section: Introductionmentioning
confidence: 99%